Presic Type Fixed Point Theorem for Four Maps in Metric Spaces - K. P. R. Rao; Sk. Sadik; S. Manro (Journal of Mathematics)
We obtained a Presic type fixed point theorem for two pairs of jointly 2k-weakly compatible maps in metric spaces. We also have given an example to illustrate our main theorem.